A Multidimensional Analytical Approach for Identifying and Locating Large Utility Pipes in Underground Infrastructure. (8th June 2015) - Tavakoli Taba, Seyedamir; Rahnamayie Zekavat, Payam; Alipour Esgandani, Golnaz; Wang, Xiangyu; Bernold, Leonhard
The population growth, technological improvements, and the need for repairing old or installing new utilities result in a high demand for trenching and drilling activities. However, penetrating the subsurface incurs the risk of damaging existing underground facilities because they were not properly documented, if at all. Ground Penetrating Radar (GPR) constitutes a well-established technology that uses electromagnetic waves to identify objects underground by detecting their reflections. The work presented in this paper focuses on the timing and other characteristics of radar pulses reflected from the buried utilities. It is hypothesised that integrating the knowledge of construction practice, geophysical principles, and electromagnetic wave propagation behaviour in various soil conditions will improve the reliability and accuracy of GPR. This paper presents the results of field experiments that studied the effects of large void such as sinkholes or drainage pipes in several undergrounds. It provides important insights into the features and patterns that can be used to improve current methods.